History of Friedrich II of Prussia $1 (BVolume 13s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 13" by Thomas Carlyle is part of a biographical work published between 1858 and 1865. This thirteenth volume completes Carlyle's monumental six-volume life of Frederick the Great of Prussia, a project that consumed thirteen years of the author's life. Drawing on extensive research, battlefield visits, and countless German sources, Carlyle crafted what contemporaries praised as a masterwork of literary genius$1 (Bfilled with wit, vivid character portraits, and dramatic battle scenes that military students studied for decades. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786